2023
DOI: 10.1039/d2sm01580c
|View full text |Cite
|
Sign up to set email alerts
|

The role of non-affine deformations in the elastic behavior of the cellular vertex model

Abstract: The vertex model of epithelia describes the apical surface of a tissue as a tiling of polygonal cells, with a mechanical energy governed by deviations in cell shape from preferred...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 48 publications
(149 reference statements)
1
11
0
Order By: Relevance
“…Please see appendix A for details. Similar analysis was done in [27] for a slightly different shape parameterization.…”
Section: Hexagonal Modelmentioning
confidence: 74%
See 3 more Smart Citations
“…Please see appendix A for details. Similar analysis was done in [27] for a slightly different shape parameterization.…”
Section: Hexagonal Modelmentioning
confidence: 74%
“…To determine the elastic moduli in mean field, we have implemented a similar deformation protocol in [27], which is a basic linear deformation for an affine transformation (see figure 7). In two dimensions, this can be expressed by Fx i + g with g = 0 and i is the index of a vertex of a polygon.…”
Section: Methods: Deformation Protocol and Determining Elastic Modulimentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, hexagonal cells can also respond via non-affine deformations, which are known to reduce the shear and Young's moduli in the incompatible regime. 16 In this study we preclude non-affine pathways for cell response as our previous work showed this approximation captures well the response to isotropic compression/dilation. 3…”
Section: Mean-field Theory Of Ordered Vertex Modelmentioning
confidence: 99%